Utilization of disused airfields of Bangladesh both during peace and war (Defense and Security Studies, 2022)
Airpower played a vital role in shaping the result of the Second World War. As a British colony, the Indian Sub-continent was targeted by Imperial Japan. The Japanese Forces came up to Myanmar (the then Burma) and their next target was the Indian sub-continent. Due to the geographical location Bangladesh (the then Bengal) was on the front line of British defense; as it was strategically important for Japan to occupy Bangladesh. As such, Bangladesh air space was highly contended by the belligerents. To support air operations, a good number of airfields were prepared by the British-led forces in the then Bengal. However, after the war, most of those airfields were abandoned. British left the region in 1947 and Bengal became part of Pakistan. Economic, strategic, and political factors did not permit the maintenance of those airfields and most were left as it was. Only Tejgaon airfield was used by Pakistanis for both civil and military aviation purposes. After the independence of Bangladesh in 1971, an effort was made to revive some of those airfields.